Post-COVID-19 Myelitis Manifesting as Partial Brown-Séquard Syndrome - Silva, Cristiana (2024)
Myelitis is a rare neurological complication of COVID-19. We will describe a patient with post-COVID-19 myelitis manifesting as partial Brown-Séquard syndrome. A 33-year-old male presented with progressive weakness of the lower limbs, evolving over the previous week. Six weeks before, the patient had had COVID-19, from which he had already recovered. Neurological examination revealed right lower limb weakness and reduced pain sensation on the left lower limb, with a T5-T6 sensory level. Thoracic magnetic resonance imaging (MRI) revealed a right intra-medullary lesion spanning from T3 to T4 with T2 signal hyperintensity. Cerebrospinal fluid study was normal, and SARS-CoV-2 was undetected. After excluding active infection, the patient received methylprednisolone and the symptoms improved. One month later, the neurological exam was considered normal and there was a significant lesion reduction on MRI. SARS-CoV-2 infection should be considered as a possible aetiology for myelitis in all patients, even in those with mild infection or asymptomatic.